The Influence Of Drug Availability, Prescription Waiting Time, And Drug Information Provision On Outpatient Loyalty At Al Mucthar Islamic Hospital, Karawang - Saputri, Eka Oktaviani; Rinaldi, Enrico Adhitya; Ambarini, Tinon; Agustin, Dinni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2024)
Background : Patient loyalty is a crucial aspect of the sustainability of pharmacy services in hospitals. Factors such as drug availability, pharmacy service waiting time, and drug information provision can influence patient satisfaction and loyalty. This study aims to analyze the influence of these three factors on outpatient loyalty at RS Islam Al Mucthar Karawang. Method: This research employs a quantitative method with a cross-sectional approach. A total of 96 outpatients were selected using purposive sampling. Data was collected through questionnaires and analyzed using the Chi-Square test for bivariate analysis and multiple logistic regression for multivariate analysis. Results: Bivariate analysis showed that drug availability (p = 0.012) and pharmacy service waiting time (p = 0.007) significantly influence patient loyalty, while drug information provision does not (p = 0.094). Multivariate analysis using multiple logistic regression revealed that, simultaneously, drug availability and waiting time for prescription services affect patient loyalty, while drug information provision does not have a significant influence. Conclusion: Improving drug availability and reducing pharmacy service waiting times can enhance patient loyalty to hospital pharmacy services. Although the provision of drug information did not significantly affect patient loyalty, it should still be improved to support patient adherence in medication use. Keywords: Drug Availability, Prescription Waiting Time, Drug Information, Patient Loyalty